Mites of the genus Gaeolaelaps (Acari: Laelapidae) from southern Brazil, with description of two new species - Marticorena, Jorge L. M.; Moreira, Grazielle Furtado; de Moraes, Gilberto José (Zootaxa, 2020)
Gaeolaelaps Evans & Till is a laelapid genus composed of free living mites, some of which have been produced commercially for use as biological control agents of pest organisms. They are edaphic and poorly known in Brazil, from where a single species has so far been reported (Gaeolaelaps aculeifer (Canestrini)). The objective of this paper is to report the occurrence of three other species from this country, two of which are new to science (G. azul n. sp., G. cerrii n. sp. and G. circularis Hyatt).